Teaching Children with Autism to Ask Questions - Squires, Katie E.; Bickel, Alyssa (Journal of the American Academy of Special Education Professionals, 2015)
Children with autism have impairments in communication that make it difficult for them to acquire the ability to ask appropriate wh- questions. This is a very important skill, and one that clinicians often do not know how to target. Search terms were entered into several databases to locate studies published in peer-reviewed journals. The studies had to include a wh- question as the dependent variable. Thirteen studies were located and described. This article reviews the literature in regards to teaching children with autism to ask questions and provides opportunities for clinicians to obtain an evidence-base from which to build their practice.